Personality attributes and personal characteristics affecting job commitment of officers and men of Nigeria Police Force (2013)
"Research in the job commitment literature has focused less attention on commitment of employees in protective service organizations, in spite of the fact that global security challenges may have affected the level of commitment of security personnel. The present study extended prior job commitment literature by examining personality attributes (cynicism) and personal characteristics as factors affecting job commitment of personnel of Nigerian Police Force. Using a cross-sectional survey design, three hundred and twelve (n=312) police personnel, consisting of 237 males and 75 females purposively selected participated in the study. Forty seven (47) respondents belonged to the officer cadre, while two hundred and sixty five (265) were non-officer cadre. A structured questionnaire comprising three sections; demographic information, cynicism scale and job commitment scale was used for data collection. Three hypotheses were generated from review of relevant literature and tested using t-test of independence. Results showed that cynicism had significant influence on job commitment, (t (310) =2.042, p<.05); cadre had significant influence on job commitment, (t (310) = 3.169, p<.05). There was no significant gender difference in job commitment, (t (310) = -.088, p>.05). The study concluded that cynicism predicted job commitment, and recommends personality profiling of prospective candidates as part of recruitment regime into the Nigeria Police Force. "